Gênero e a representação de mulheres em conselhos municipais de Pato Branco - Paraná - Preslak, Juliane (2018)
This case study seeks to analyze the interaction between gender and county councils, in order to determine if the gender perception of representatives of civil society is reflected in the presence or absence of proposals with the county councils of Rural Development (CMDR) and Food and Nutrition Security (COMSEA), in the municipality of Pato Branco, Paraná, in the management from 2015 to 2017. These councils were selected because of the exploratory data collection focused on the representative distribution of women in the councils of the municipality, with COMSEA majority of women representatives and the CMDR the minority of women representatives. Not coincidentally, the guidelines of these councils are related to food in terms of production, access and consumption, and the sexual division of labor in these activities becomes clear. In addition, the theoretical debate is based on the complex relations of the modern world and the oppressions experienced by women, as well as the hierarchy and disparities between the sexes, classes, knowledge and peoples, which are understood as part of the same Eurocentric matrix, disembodied from their original (European) territories and distributed throughout the globe, radicalized by the process of globalization. In this context, councils emerge as agents that promote the participation and representation of women in institutional politics. Thus, it can be affirmed that in the trajectory of the counselors there was no finding of connection with the feminist struggle flags. However, the fact that representatives of civil society are women, has made it possible to connect the discussions that demonstrate the councils as flexible to openness to participation and representation of women, even if the interests of women's rights are neglected and ignored, since most of the councilors are not aware of the patriarchal structure that surrounds their participation in institutionalized politics. And it is precisely this shallow perception about gender and social status of women, coupled with the low representativeness and training of the representatives, which results in the absence of women-related roles in both councils.